The old navarre book in the archival sources of the XVIIth century - Ruiz Astiz, Javier (Revista General de Información y Documentación, 2020)
The historical archives have a rich documentary corpus that allows researchers to rescue faithful testimonies about the History of the Book. To show it, this article intends to reconstruct certain aspects of the Old Book in Navarre of the seventeenth century through archival documents, such as judicial processes and notarial deeds. Thus, all kinds of information about the actors (printer, bookseller, author, editor) that intervened in the printing press of the time, the products that were published and those that were simply planned were verified. In turn, we can approach the material characteristics of navarrese print and the commercial intricacies that prevailed in the kingdom during that century.
Keywords: old book; printing; archival sources; Kingdom of Navarre; XVIIth century